Berea, Franklin County - Raitinger, Laine (Kansas State University, The Chapman Center for Rural Studies, 2012)
Just three miles east of Richmond, Kansas, in the southwest corner of Franklin County, lies a cemetery, a cemetery containing weathered tombstones barely legible as recently as a few years ago. This cemetery is almost all that remains of a short lived town called Berea. Geographically, Berea was located at Latitude: N 38° 23' 56.8463" and Longitude: W 95° 10' 51.2833. Although the life of Berea as a town was short lived, the people and institutions established in the community over the years have made the legacy of Berea continue.
Laine Raitinger, “Berea, Franklin County,” Chapman Center Research Collections,https://ccrsresearchcollections.omeka.net/items/show/7..
Keywords: Berea; Berea United Presbyterian Church; Franklin County; Butler Road; Underground Railroad; James N. Smith